Accounting Students’ Performance in Distance Education: A Study Focused on Sociodemographic Factors - Nasu, Vitor Hideo (Journal of Information Systems and Technology Management, 2020)
This study aimed to investigate the relationship between accounting students’ performance and sociodemographic variables (namely gender, employment, marital status, and ethnicity) in distance education. I collected data from the 2015 National Exam of Students’ Performance, obtaining a final sample of 11,707 observations. Results indicated that male students outperformed female ones. Also, worker students have better performance than their colleagues. Married students obtained better performance than their single colleagues, but no relevant difference was found in comparison to other (divorced, widowed, etc.) students. Regarding ethnicity, white students outperformed other students (black, brown, and others).